Hubungan status gizi dengan kejadian amenorrhea pada wanita usia subur (20-35 tahun) - Dea Riskha Fitriliana; Pedvin Ratna Meikawati (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: One of the important factors influencing the incidence of amenorrhea is nutritional status, which reflects the balance between energy intake and the body's energy needs. Purpose: To analyze the relationship between nutritional status and the incidence of amenorrhea among women of reproductive age (20–35 years), in Pasarbatang Subdistrict, Brebes District, Brebes Regency. Method: This is an analytical study with a cross-sectional approach. The population consisted of women of reproductive age in the area. A total of 81 respondents who experienced amenorrhea and met the inclusion criteria were selected as the sample. The statistical test used was the Chi-Square test. Results: The Chi-Square test yielded a calculated X² value of 7.342 with degrees of freedom (df) = 2 and a 5% significance level, resulting in a table X² value of 5.991. Since the calculated X² is greater than the table value (7.342 > 5.991) and the p-value = 0.025 (p < 0.05), it indicates a significant relationship between nutritional status and the incidence of amenorrhea. Conclusion: There is a significant relationship between nutritional status and the incidence of amenorrhea among women of reproductive age (20–35 years) in Pasarbatang Subdistrict, Brebes District, Brebes Regency.